Development of Ranking Criteria to Determine The Emergency Auxiliary Spillway for Dam Overtopping Failure - Muda, R. S.; Kamal, N. S.; Norkhairi, F. F.; Ismail, M. N. (International Journal of Integrated Engineering, 2025)
Dams are critical infrastructure for sustaining human life by serving various purposes, including irrigation and water supply, power generation, flood mitigation, and other essential needs. In the event of a dam failure, the sudden release of stored reservoir water can have catastrophic consequences to downstream communities and the environment. Dam failure is often caused by overtopping, which happens when the water level in the reservoir exceeds the dam's capacity. In preventing overtopping, considering an auxiliary spillway as an additional passage for releasing surplus water from the dam or reservoir during periods of high water flow or flooding emerges as a viable option. This study focuses on developing comprehensive ranking criteria for systematically determining emergency auxiliary spillways, explicitly addressing the potential threat of dam overtopping failures. It employs a structured methodology to establish robust criteria for evaluating and prioritizing potential sites. The study applied a multidisciplinary approach in assessing topography, geology, geotechnical aspects, river capacity, feasibility, technical intricacies, accessibility, construction limitations, site seismic activity, environmental ramifications, and the population at risk. The study employed multi-criterion analysis (MCA) to establish ranking criteria, enabling the prioritization of the most suitable saddle dams for selection as emergency auxiliary spillways. The study chose a Hydropower scheme situated in the Eastern region of Peninsular Malaysia for a case study. This scheme comprises a main dam and eight saddle dams within its infrastructure. The outcomes of this study contribute significantly to the advancement of methodologies for selecting emergency auxiliary spillways, thereby enhancing dam safety measures and minimizing the potential risks associated with overtopping incidents.